Karakteristik plasma lucutan berpenghalang dielektrik isian gas Nitrogen - Febry Fitriani; Muhammad Nur; Fajar Arianto (Youngster Physics Journal, 2017)
Research on the characteristics of the dielectric barrier discharge filled with Nitrogen gas fields has been done. The plasma reactor that used in this study formed by a spiral-shaped cylindrical electrode component. Spiral electrode is made of copper wire with 72 windings and 25.05 mm of diameter, while the cylindrical electrode from copper sheets are glued on the walls of the outer tube diameter of 0,27 mm with a length of 25 cm. The dielectrics that used is pyrex with a length of 30 cm, a diameter of 3 cm, and a thickness of 2,45 mm. Characterization of dielectric barrier discharge plasma is used to determine the working area of the reactor and knowing the initial voltage to the emergence of the current as a sign of discharge. This characterization was done with Nitrogen gas field, which is a variation of voltage used is from 0,4 to 1.2 kV with a rise of 0.2 kV interval and Nitrogen flow rate of 2-8 L /min with intervals increase of 1 L/min. Result in the discharge flow 7 L/min with the lowest mobility value of 58.300 m2/V.s and the discharge flow 4 L/min with the highest mobility value of 91.600 m2/V.s. Therefore, it can be concluded that the greater the saturation current value, the greater the value of the ion mobility (μ).Keywords: Dielectric barrier discharge plasma, Characteristics of dielectric barrier discharge plasma, Mobility of charge carriers.